Di Antara Keterjangkauan dan Nilai Keislaman: Pengaruh Kesenjangan Ekonomi terhadap Pilihan Sekolah Dasar Islam - Achmad Baidowi; Su'udi Su'udi; Akhmad Syafiudin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Primary education constitutes an essential foundation for human capital development and serves as a central catalyst for socio-economic mobility within society. This study aims to comprehensively analyze cultural preferences, academic expectations, and the community’s purchasing power (Willingness to Pay) regarding primary school models in the Genteng, Glenmore, and Kalibaru areas of Banyuwangi Regency. Using a quantitative approach through a field survey method, the study involved 100 parent respondents. The findings reveal a market anomaly and polarization that leave a gap within the middle segment (the “Missing Middle”). The data indicate the dominance of lower-middle-income groups (87.78%) characterized by single-income households, which set the monthly tuition fee (SPP) affordability threshold at an equilibrium point of IDR 50,000–100,000 (85.56%). A striking paradoxical finding emerges: while 64.44% of respondents aspire to high-quality school models (Islamic Integrated Primary Schools/Islamic boarding schools) with a primary focus on moral and character development (93.33%), 71.11% empirically reject a full-day school system and instead prefer a half-day schedule. These findings underscore the urgency of establishing a “middle-path” educational institution capable of deconstructing an integrated curriculum into an efficient time structure (Half-Day Integrated School), supported by financial engineering schemes such as installment-based payment systems (92.22%), as well as the provision of school transportation services to mitigate geographical barriers and parents’ psychographic concerns